An Ophthalmology Virtual Externship during the COVID-19 Pandemic: A Pilot Study - Dirani, Karim; Tajran, Jahan; Tur, Komalpreet; Craig, Annmarie; Freedman, Ryan L.; Uddin, Niyaz; Kim, Chaesik; Ross, Bing X.; Juzych, Mark S.; Goyal, Anju (Journal of Academic Ophthalmology, 2023)
Background The evolution of medical school curricula, characterized by truncated preclinical periods and reduced emphasis on ophthalmology, presents formidable obstacles to early exposure for aspiring medical students. The constraints imposed by the coronavirus disease 2019 pandemic further exacerbated the limitations on opportunities, compelling the implementation of innovative initiatives aimed at augmenting students' ophthalmology education through virtual means.Purpose This article assesses the impact of an Ophthalmology Virtual Externship (OVE) on medical students' knowledge, interest, confidence, and seeking mentorship in ophthalmology.Materials and Methods A total of 76 students voluntarily participated in the program. The OVE encompassed four virtual sessions, facilitated by 4th year medical students employing a near-peer mentorship framework. The initiative was tailored for 2nd and 3rd year medical students and was conducted under the supervision of a faculty member. All participating students completed both pre- and postexternship surveys utilizing a 7-point Likert scale to gauge their levels of interest, confidence, and inclination toward mentorship opportunities in the field of ophthalmology. Furthermore, assessments of ophthalmology knowledge were administered prior to and subsequent to the externship participation. The degree of satisfaction derived from the OVE experience was also evaluated.Results Participation in the OVE significantly elevated confidence in knowledge (p < 0.001) and mentorship interest (p = 0.029). Ophthalmology knowledge test scores also notably improved post-OVE across all participants, irrespective of prior experience (p < 0.001), with the most significant increase observed among 2nd and 3rd year students (p < 0.0001). After OVE participation, 73% of students expressed intent to pursue ophthalmology opportunities, including mentorship or research. The OVE received an average Likert score of 6.35 out of 7 for student satisfaction.Conclusion The OVE serves as a virtual learning instrument beneficial for 2nd and 3rd year students with a proclivity for ophthalmology, offering a means to circumvent curriculum-related constraints. Moreover, given the decline in formal ophthalmic education, our study contributes to future research assessing the effectiveness of an OVE in addressing ophthalmic knowledge gaps among all medical students.
Keywords: virtual externship; ophthalmology; confidence; mentorship